RUSSIAN ETATISM AND RUSSIAN PATERNALISM IN THE POLITICAL PROCESS OF RUSSIA ON THE EVE OF PETER THE GREAT’S REFORMATION - N. A. Omelchenko (Вестник университета)
The article сonsiders ideological, political and cultural prerequisites of the Peter the Great state reforms that, according to the author, were formed long before the Peter`s Reformation, and had a significant impact on the course and model of the “regular” (military- police) state created by Peter the First. Among the main prerequisites are the etatization (nationalization) of society and the associated paternalistic nature of state relations, which formed the traditional foundations of national statehood and strengthened in the 17th century in the context of Russia’s withdrawal from the Turmoil and the restoration of the national statehood destroyed in the time of troubles. The paper investigates the reasons for the formation of these features of the development of national statehood, the main of which the author proposes to search in the civilizational and geopolitical features of the formation and evolution of the Russian state, the weakness of the institutional foundations of Russian politics, stylistic peculiarities of Russian Orthodoxy and a number of other factors.